2005
DOI: 10.1093/jjco/hyi067
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Factor-1α is Associated with Risk of Aggressive Behavior and Tumor Angiogenesis in Gastrointestinal Stromal Tumor

Abstract: Our findings suggest that HIF-1alpha may play an important role in aggressive behavior and tumor angiogenesis in GIST. In addition, high expression of HIF-1alpha was significantly correlated with tumor recurrence/distant metastasis, so it may provide an ancillary prognostic factor for GIST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 34 publications
4
59
0
Order By: Relevance
“…However, 16 of 25 of patients had been treated with more than two prior TKIs before study entry. The nine patients in our study who were treated with pazopanib as third-line therapy received a median of two cycles [1][2][3][4][5][6][7][8][9] which is comparable with nilotinib, but inferior to regorafenib [1][2][3]. The fact that our patients were heavily pretreated with multiple TKIs may have affected the outcome of this trial possibly due to multiple secondary mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 16 of 25 of patients had been treated with more than two prior TKIs before study entry. The nine patients in our study who were treated with pazopanib as third-line therapy received a median of two cycles [1][2][3][4][5][6][7][8][9] which is comparable with nilotinib, but inferior to regorafenib [1][2][3]. The fact that our patients were heavily pretreated with multiple TKIs may have affected the outcome of this trial possibly due to multiple secondary mutations.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that hypoxia-induced factor (HIF-1α) is overexpressed in SDH-deficient GIST and can subsequently lead to increased angiogenesis through regulation of VEGF [7,8]. HIF-1α is also associated with development of metastatic disease in GIST [9].…”
Section: Discussionmentioning
confidence: 99%
“…Both groups reported that increased VEGF tumor expression correlated with inferior outcome, including an increased likelihood of developing liver metastases. 13,14 Another group used an enzyme-linked immunosorbent assay (ELISA)-based method to determine tumor VEGF levels more quantitatively in 115 patients with soft-tissue sarcoma. 5 Higher tumor VEGF levels correlated with higher tumor stage, higher tumor grade, and increased risk of local and distant tumor recurrence.…”
Section: Soft-tissue Sarcomamentioning
confidence: 99%
“…Besides, it was shown that genetic mutations promoting overstabilization of HiF-1α are a feature of various types of cancers [8]. Finally, it is suggested that the intracellular level of HiF-1α can be related to the aggressiveness of the tumors [53,24,4,10] However, up to now, mathematical models describing the G1/S transition under hypoxia, did not take into account the HiF-1α factor in the hypoxia pathway.Therefore, we propose a mathematical model of the G1/S transition under hypoxia, which explicitly integrates the HiF-1α pathway. The model reproduces the slowing down of G1 phase under moderate hypoxia, and the entry into quiescence of proliferating cells under severe hypoxia.…”
mentioning
confidence: 99%